2015
DOI: 10.1515/med-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal right hepatic artery injury resulting in right hepatic atrophy: diagnosed by laparoscopic cholecystectomy

Abstract: An intact hepatic artery is the gateway to successful hepato-biliary surgery. Introduction of laproscopic cholecystectomy (LC) has stimulated a renewed interest in the anatomy of hepatic artery. In this case report we have highlighted importance of variations of right hepatic artery in terms of origin and course We present a rare asymptomatic case of liver atrophy due to an intraoperative lesion of right hepatic artery. We also performed a literature review about surgical vascular lesions and tried to confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The earlier LC studies demonstrated an anomaly of right hepatic artery and were being disrupted during excessive hemorrhage throughout Calot's triangle dissection [27]. The outline with the surgery described the explanation for blood loss and also the intra-operative management with unspecified amounts of clips [27]. Ding et al, witnessed aberrant RHA in 18 (3%) of cases in their study [4].…”
Section: Aberrant Right Hepatic Artery (Rha)mentioning
confidence: 97%
See 1 more Smart Citation
“…The earlier LC studies demonstrated an anomaly of right hepatic artery and were being disrupted during excessive hemorrhage throughout Calot's triangle dissection [27]. The outline with the surgery described the explanation for blood loss and also the intra-operative management with unspecified amounts of clips [27]. Ding et al, witnessed aberrant RHA in 18 (3%) of cases in their study [4].…”
Section: Aberrant Right Hepatic Artery (Rha)mentioning
confidence: 97%
“…According to recent publicized research, focusing on the patients with combined bile duct and hepatic artery injuries during LC revealed, formation of liver abscesses in three of four cases and stricture's anastomotic site by 50% of four sufferers; on the other hand, these complications just weren't recognized in cases with separated biliary duct injuries [26]. The earlier LC studies demonstrated an anomaly of right hepatic artery and were being disrupted during excessive hemorrhage throughout Calot's triangle dissection [27]. The outline with the surgery described the explanation for blood loss and also the intra-operative management with unspecified amounts of clips [27].…”
Section: Aberrant Right Hepatic Artery (Rha)mentioning
confidence: 99%